Mucinous Carcinomatosis: A Rare Association between an Ovarian Tumor and an E-GIST - Hugo Palma Rios; André Goulart; Pedro Leão (Case Reports in Surgery)
Pseudomyxoma peritonei (PMP) and extragastrointestinal stromal tumors (E-GISTs) are both rare entities. Most of the time, PMP is associated with an appendiceal tumor. An ovarian mucinous tumor can mimic appendiceal metastases. E-GIST is a mesenchymal tumor that can arise from the omentum, retroperitoneum, mesentery, or pleura. We present a case of an 87-year-old woman with mucinous carcinomatosis and acute intestinal occlusion submitted to an emergency laparotomy. She has found to have a borderline mucinous tumor of the ovary from the intestinal type with several lesions of pseudomyxoma peritonei and an E-GIST from the epiploons retrocavity (intermediated risk). In the literature, no relation was found between these two rare tumors. E-GIST was an incidental finding in the context of a mucinous carcinomatosis.